Prospective evaluation of CYP19A1-mediated aromatase inhibitors for ER+ breast cancers by ultra-high performance liquid chromatography tandem mass spectrometry supported by in silico methods - N.J. Gumede; K. Bisetty; L. Escuder-Gilabert; M.J. Medina-Hernandez; S. Sagrado (Results in Chemistry)
Human aromatase (CYP19A1) is a membrane-associated microsomal cytochrome P450 enzyme that is responsible for facilitating the conversion of androgens into estrogens. Aromatase inhibitors (AIs) are widely utilized in the management of breast cancer, and the CYP19A1 aromatase is acknowledged as a validated target for therapeutic intervention in estrogen receptor positive (ER+) breast cancer. In this study, we assessed the efficacy of 13 compounds in inhibiting CYP19A1-mediated aromatization using ultra-high-performance liquid chromatography tandem mass spectroscopy (UHPLC-MS/MS). Compound 12 emerged as the most potent inhibitor, with an IC50 of 3.5 μM. A selectivity assay involving the CYP17A1 enzyme and five major CYP450 isoforms further demonstrated that compound 12 exhibited significant selectivity for CYP19A1. This finding suggests that compound 12 could be considered a potential lead for subsequent hit-to‑lead optimization, offering a novel scaffold compared with other compounds currently in various stages of clinical development. Additionally, molecular docking analyses were conducted on the compound 12-CYP19A1 complex, both with and without the imposition of metal constraints. Docking with metal constraints validated the binding network, revealing strong hydrogen bonds with ASP309, MET374, and a metal ligand coordination between the heme iron atom of CYP19A1 and compound 12. We have performed Structure Activity Relationship (SAR) studies on compound 12, however the results cannot be disclosed for now since they are patent pending. Thus, the current work can be considered as a prospective study.